2016
DOI: 10.1007/s10816-016-9276-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Handaxe Size and Shape on Cutting Efficiency: A Large-Scale Experiment and Morphometric Analysis

Abstract: Handaxes represent one of the most temporally enduring and geographically widespread of Palaeolithic artifacts and thus comprised a key technological strategy of many hominin populations. Archaeologically observable variation in the size (i.e., mass) and shape properties of handaxes has been frequently noted. It is logical to ask whether some of this variability may have had functional implications. Here, we report the results of a large-scale (n = 500 handaxes) experiment designed to examine the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 73 publications
5
28
0
Order By: Relevance
“…The most commonly cited targets for improved diet quality are large vertebrate carcasses and large plant underground storage organs, resources nonhuman primates do not exploit systematically or in bulk . Experiments engaging professional butchers and others in the use of reproductions of LCTs rate those artifacts as highly effective . Few recent humans use stone tools to dig up roots and tubers, but before they acquired metal tools many of them used stone implements to carve digging sticks out of tropical hardwoods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly cited targets for improved diet quality are large vertebrate carcasses and large plant underground storage organs, resources nonhuman primates do not exploit systematically or in bulk . Experiments engaging professional butchers and others in the use of reproductions of LCTs rate those artifacts as highly effective . Few recent humans use stone tools to dig up roots and tubers, but before they acquired metal tools many of them used stone implements to carve digging sticks out of tropical hardwoods.…”
Section: Resultsmentioning
confidence: 99%
“…110 Experiments engaging professional butchers and others in the use of reproductions of LCTs rate those artifacts as highly effective. 111,112 Few recent humans use stone tools to dig up roots and tubers, but before they acquired metal tools many of them used stone implements to carve digging sticks out of tropical hardwoods.…”
Section: Flaked Stone Celts Similar To Recent Woodcutting Tools Appeamentioning
confidence: 99%
“…). Indeed, previous research has indicated that shape, size and symmetry (Key and Lycett ; Machin et al . ) have only limited impact on a handaxe's ability to be used as a cutting tool; at least until morphological ‘thresholds’ are reached (Key and Lycett ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has indicated that shape, size and symmetry (Key and Lycett ; Machin et al . ) have only limited impact on a handaxe's ability to be used as a cutting tool; at least until morphological ‘thresholds’ are reached (Key and Lycett ). As experimentally confirmed elsewhere, however, some specific tool‐form attributes do have significant influences on stone tool performance (e.g., Clarkson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation